Kepemimpinan Transformatif dan Partisipatif Kepala Sekolah dalam Menumbuhkan Literasi Siswa SD Negeri Beji 01: Transformative and Participatory Leadership of the Principal in Fostering Student Literacy at SD Negeri Beji 01 - Ardhina Maya Nugraheni; Senowarsito Senowarsito; Rosalina Br Ginting (ITScience (Information Technology and Science), 2026)
School principals play a crucial role in implementing and overseeing literacy programs to ensure their success. While principals are highly motivated to foster a literacy culture, not all have systematic managerial strategies for developing students' literacy skills. This study aims to describe the principal's transformative and participatory leadership regarding: (1) planning; (2) organizing; (3) implementation; and (4) supervision in the context of fostering students' literacy skills. A descriptive qualitative approach was employed. The data included descriptions, perspectives, experiences, policies, and the principal's application of transformative and participatory leadership to enhance students' literacy skills. Data collection involved observation, interviews, and documentation at SD Negeri 01 Beji, East Ungaran District. Data analysis followed stages of data reduction, data presentation, and conclusion drawing, using triangulation techniques to ensure data validity. The results indicate that: (1) literacy program planning involved coordination meetings, budget preparation, goal setting, and problem identification; (2) organizing involved task allocation based on competence, delegation of authority, formation of management teams, and the drafting of job descriptions; (3) implementation was realized through pre-lesson reading activities, library visits, the LITERAKSI program, literacy corners, and reading walls; and (4) supervision was conducted through direct supervision, classroom visits, and school committee oversight.